Analysis of User Satisfaction on Batam Online Supermarket Application in Batam - Jimmy Pratama (JTKSI (Jurnal Teknologi Komputer dan Sistem Informasi), 2022)
Pandemic Covid-19 is going on in Indonesia have a major impact changing patterns of consumption of goods and services from offline to online. The distance restrictions that must be carried out to prevent the spread of Covid-19 transmission and break the chain of the spread of this virus, require the public to avoid crowds from crowded places. The presence of the Batam Online Supermarket online market application in the city of Batam is certainly one of the efforts to prevent Covid-19 and as an example of the rapid development of digitalization of technology. The biggest challenge in the market online lies in customer satisfaction, so this research adopts the Technology Acceptance Model (TAM) and D&M IS Success Model. Of the 370 respondents who were obtained from the Slovin formula and taken using probability sampling technique, then they were tested for validity test analysis, reliability testing, multiple regression analysis and hypothesis testing, t test and F test on variables using SPSS 23. Based on the result, this study showed that the variable of system quality, information quality, service quality were significant on the user satisfaction, meanwhile the variable of perceived easy of use and perceived usefulness were not significant on the user satisfaction in using BOS application.